Parasitism induces negative effects of physiological integration in a clonal plant. Issue 1 (23rd September 2020) - Gao, Fang‐Lei; Alpert, Peter; Yu, Fei‐Hai
Summary: Clonal integration often increases fitness of clonal plants, but it may decrease it when some but not all connected plants (ramets) within a clone are parasitized. This hypothesis was synthesized in a conceptual model and tested by growing pairs of connected ramets of two congeneric clonal plants, Sphagneticola trilobata and Sphagneticola calendulacea, with and without parasitizing one ramet with Cuscuta australis and with and without severing the connection (allowing or preventing integration). Consistent with the model, integration in S. calendulacea did not affect biomass of the parasitized ramet, decreased biomass of its connected, unparasitized ramet by 60% and of the clone by 40%, and increased biomass of the parasite by 50%. By contrast, integration in S. trilobata did not affect biomass of the clone or the parasite. The parasite increased export of nitrogen‐15 from the connected, unparasitized ramet seven‐fold in S. calendulacea but did not affect export in S. trilobata . Parasitism can cause clonal integration to negatively affect fitness in clonal plants because parasites can import resources from connected, unparasitized ramets, possibly partly through signaling. This is the first experimental demonstration that clonal integration can decrease fitness in plants induced by parasitism and may help explain community‐level effects of parasites.